Astronomia e astronáutica em uma abordagem contextualizada para o ensino de química - Otaviano, Cristyam David Costa (2019)
Education, in general, has undergone several changes. The schools now have highly connected students and a rather mechanical teaching. The contextualization can be a great methodology of teaching of Sciences, in front of this problematic, as well as the incorporation of Digital Technologies of Communication in the classroom environment, as well as the teaching practice. For this, this work brings a contextualization of Chemistry from Astronomy and Astronautics, considering the little use of these sciences in the classroom, especially with regard to the teaching of Chemistry. Developed at the Federal Institute of Science and Technology of Ceará, Campus Caucaia, with students approximately 80 students of the first semester of concurrent technical courses of Electroelectronics and Petrochemisrty. This work brought from a Qualitative, Quantitative and Exploratory analysis, an understanding of the degree and level of knowledge, students' profile and their interest in Chemistry, as well as data on the use of Digital Communication Technologies to complement and assist the teaching-learning process. During five meetings, each of two hours, the contents of Atomic Models, Periodic Properties and Chemical Bonds were addressed, through a contextualization with Astronomy, Astronautics and History of Sciences, using in addition to this methodology multidisciplinary and interdisciplinary, as well as as having support of Digital Information Technology of the Communication as helpers in the process of teaching and learning. At the end of the study, we analyzed and compared the students' initial and final behavior. With this we noticed an increase in students' interest in Chemistry and in the work theme, as well as a great receptivity of the students with the use of technologies during the classes, so that Digital Communication Technologies of Communication good assistants in the process of teaching- learning within the context of this work. Keywords: Astronomy. Astronautics. Chemistry. Contextualization. History of Sciences. History of Astronomy. History of Astronautics. Digital Communication Technologies. Atomic models. Chemical bonds. Periodic properties.